Influence of Promotional Prospects on Turnover Intentions of Public Secondary School Teachers in Meru County - Peter Kalunge Ekabu; Grace Nyagah; Jeremiah.M. Kalai (European Scientific Journal, ESJ, 2018)
The importance of motivation in retaining core employees and reducing turnover intention in any organization cannot be underestimated. Therefore, retaining the best teachers in secondary schools continue to be a major challenge for educational managers in Kenya as teachers keep changing careers or are not fully committed to their duties because psychologically majority have their hearts elsewhere. This study aimed at examining the influence of promotional prospects on turnover intentions of public secondary school teachers in Meru County. The study used a descriptive survey design with both quantitative and qualitative approaches in data collection and analysis. A total of 520 respondents were involved in the study. Teacher promotional prospects, was examined to determine its relationship with the dependent variable, turnover intentions. Data obtained from questionnaires were analyzed quantitatively using SPSS version 21. Hypothesis was tested using Pearson product moment correction coefficient and chi-square goodness of fit at 95%, p<0.05. The results from product moment correction showed that the independent variable; promotional prospects (r=-0.524, p<0.001), has a negative and an inverse relationship with the dependent variable, turnover intention. The Chisquare analysis corroborated the Pearson correlation results by showing a significant relationship between promotion prospects and turnover intentions of secondary school teachers in Meru County. The results concluded that teachers’ motivation in secondary schools in Meru County is low with teachers having poor morale and low levels of commitment to their job due to lack of promotion and stagnation in one grade hence high turnover intentions set in. The study recommends that the Teachers Service Commission of Kenya, consider issues of promotion of teachers in motivating and reducing turnover intentions hence retention in teaching service.